Dexmedetomidine pretreatment enhances protective effect efficacy of pericytes agaist acute lung injury in septic mice - LUO Xi; ZHANG Zisen; YANG Ao (陆军军医大学学报)
Objective　‍To investigate the effect and mechanism of dexmedetomidine （Dex） pretreated pericytes （Dex-PCs） on acute lung injury （ALI） in septic mice.Methods‍　‍Mouse model of sepsis-ALI was established with intraperitoneal injection of lipopolysaccharide （LPS） at a dose of 10 mg/kg. A total of 96 C57BL/6J mice were randomly divided into sham operation （Sham） group， ALI group， PC treatment group and Dex-PCs treatment group. The mice of the PCs and Dex-PCs groups received a tail venous injection of 5×105 PC cells， respectively， whereas those of the Sham and ALI groups received equal volume of normal saline. Flow cytometry， immunofluorescence assay， whole-body volume tracing system and ELISA were used to observe the changes in the colonization of PCs， pulmonary vascular permeability， lung function， serum TNF-α and IL-6 levels， as well as the survival rate and survival time of mice at 72 h after LPS stimulation. After PCs and Dex-PCs were exposed to 10 μg/mL LPS， the level of intracellular reactive oxygen species （ROS） was measured.　‍Results　‍Compared with the Sham group， the ALI group had increased permeability of pulmonary vascular endothelial cells， extensive extravasation of Evans blue， severely destructed of lung tissue structure and massive inflammatory cell infiltration， higher lung wet/dry weight ratio， elevated serum TNF-α and IL-6 levels， and declined lung function， and no mice survived for 72 h after modeling （P<0.05）. Both PC cell treatment effectively alleviated the pulmonary vascular endothelial leakage， reduced Evans blue content per unit tissue， improved lung pathological structure， lung function and inflammatory responses， and significantly improved the survival rates in the PC group and the Dex-PC group （P<0.05）. What’s more， the therapeutic effect of Dex-PC cells was significantly better than that of the PC cells （P<0.05）. LPS stimulation induced ROS accumulation greatly in PCs， but no such effect was observed in the PCs after Dex pretreatment （P<0.05）.　‍Conclusion　‍Dex pretreatment significantly enhances PCs’ protective effect on pulmonary vascular endothelial barrier functions in septic mice， which may be due to its enhancing anti-oxidative capacity of PCs.